Validation of the Short Version (TLS-15) of the Triangular Love Scale (TLS-45) across 37 Languages - Kowal, Marta; Sorokowski, Piotr; Dinić, Bojana M; Pisanski, Katarzyna; Gjoneska, Biljana; Frederick, David A; Pfuhl, Gerit; Milfont, Taciano L; Bode, Adam; Aguilar, Leonardo; García, Felipe E; Roberts, S Craig; et al. (Archives of sexual behavior, 2024)
Love is a phenomenon that occurs across the world and affects many aspects of human life, including the choice of, and process of bonding with, a romantic partner. Thus, developing a reliable and valid measure of love experiences is crucial. One of the most popular tools to quantify love is Sternberg's 45-item Triangular Love Scale (TLS-45), which measures three love components: intimacy, passion, and commitment. However, our literature review reveals that most studies (64%) use a broad variety of shortened versions of the TLS-45. Here, aiming to achieve scientific consensus and improve the reliability, comparability, and generalizability of results across studies, we developed a short version of the scale-the TLS-15-comprised of 15 items with 5-point, rather than 9-point, response scales. In Study 1 (N = 7,332), we re-analyzed secondary data from a large-scale multinational study that validated the original TLS-45 to establish whether the scale could be truncated. In Study 2 (N = 307), we provided evidence for the three-factor structure of the TLS-15 and its reliability. Study 3 (N = 413) confirmed convergent validity and test-retest stability of the TLS-15. Study 4 (N = 60,311) presented a large-scale validation across 37 linguistic versions of the TLS-15 on a cross-cultural sample spanning every continent of the globe. The overall results provide support for the reliability, validity, and cross-cultural invariance of the TLS-15, which can be used as a measure of love components-either separately or jointly as a three-factor measure.
Keywords: jazyk (prostředek komunikace); Psychometrics; Reproducibility of Results; láska; psychometrie; sexuální chování; reprodukovatelnost výsledků; Triangular Love Scale; sexuální partneři; průzkumy a dotazníky; Love; Sexual Partners; Sexual Behavior; Humans; Surveys and Questionnaires; Triangular theory of love; Language; Cross-cultural; lidé